Pengembangan Wisata Kesehatan Dengan Menggunakan Obat Dari Bahan Alami - Christiadi Yanuar Saputro (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This article discusses the development of health tourism potential through the use of medicines from natural ingredients. Health and wellness have become a major concern of modern society, leading to increased interest in natural treatment alternatives. In this context, this study aims to explore the potential for developing tourist destinations that combine elements of health and natural beauty with the use of traditional medicines derived from natural ingredients. The research method involves surveying the latest literature on the use of natural medicines in the health sector, as well as case studies of several tourist sites that have successfully integrated these aspects. Data analysis was carried out to identify the advantages and challenges in developing health tourism based on natural ingredients, both in terms of health benefits and economic potential. The results of the study show that the use of medicines from natural ingredients in the context of health tourism has the potential to increase tourist attractiveness, promote local culture, and provide alternative treatments that are safer and more sustainable. However, challenges such as regulation of standards, public education and maintenance of natural resources need to be overcome for this development to be sustainable. This article provides insight into the potential and benefits of developing medicine-based health tourism from natural ingredients, as well as presents a holistic view of the relationship between health, nature and local culture in the context of tourism. The practical implication of this research is to provide guidance for stakeholders in planning, managing and promoting health tourism destinations that are sustainable and beneficial to all.